Assessment Of The Effect Of Carbonated Drinks On The Surface Of Enamel Using A Scanning Electron Microscope - V S, Rakshitha; Rajaraman, Vaishnavi; Kumar, Sathish (Journal of Neonatal Surgery, 2024)
Background: Soft drink consumption has recently increased significantly. According to studies, drinking beverages with added sugar increases calorie intake, which in turn causes obesity. The findings of research reports indicated that the majority of beverages have acidic properties. As a result, prolonged exposure to such a solution may cause erosion, which would erode the hard tissues of the teeth. This study aimed to determine how carbonated beverages affect the enamel's surface. Methods: The sound teeth were collected and divided into three groups based on exposure (Group I - Pepsi + Bisleri (n=6), Group II - Coca-Cola (n=6), Group lll - Controlled (n=3)). Teeth were sterilised with 1% Hypochlorite solution and cleaned with double-distilled water using a bath sonicator. The teeth were incubated with Coca-Cola (15 mL), Pepsi (15 mL), and Bisleri (15 mL) for 7 days and 14 days. SEM and EDS analyses were performed at 7 and 14 days. Result: Compared to the Control (unexposed) group, exposed groups had more damage and loss of enamel surface at 7 days, as well as 14 days, tooth damage was more serious. In addition, compared to a single drink, combined exposure to two or more soft drinks at a particular time caused the loss of enamel structure. EDS analysis showed differences in Ca, P, O, and C wt % between the three groups. Exposed groups had less Ca, P and more C wt % compared to unexposed. This clearly suggests the detrimental effect of soft drinks on the enamel surface with longer exposure. Conclusion: Conclusively, the effect of carbonated drinks on the surface of enamel can be assessed by scanning electron microscope (SEM). Consuming two or more soft drinks at a particular time causes more damage to the enamel surface